The role of polyphenol intake and ecological awareness in shaping sustainable nutrition - Bayram, Hatice Merve; Ozturkcan, Arda (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to examine the relationship between dietary polyphenol intake, adherence to the Mediterranean diet (MD), sustainable and healthy eating behaviors, and ecological footprint awareness among Turkish adults.MethodsThis cross-sectional study was conducted in Istanbul between January–May 2024 with 197 adults. Participants completed a demographic questionnaire, the Mediterranean Diet Adherence Screener (MEDAS), the Sustainable and Healthy Eating Behaviors Scale (SHEB), the Awareness Scale for Reducing Ecological Footprint (ASREF), and a one-day dietary record. Total polyphenol intake was estimated using the Phenol-Explorer database. As the data did not follow a normal distribution, non-parametric tests (Spearman and Kruskal–Wallis) were applied.ResultsA total of 87.8% of participants showed low adherence to the MD. Mean polyphenol intake was 1,616 ± 641 mg/day. Polyphenol intake was moderately positively correlated with MEDAS scores (r = 0.456, p < 0.001) and weakly correlated with SHEB scores (r = 0.147, p < 0.05). SHEB and ASREF scores demonstrated a moderate positive correlation (r = 0.498, p < 0.001). In regression models, ecological footprint awareness emerged as the strongest predictor of sustainable and healthy eating behaviors.ConclusionDespite overall low adherence to the MD, higher polyphenol intake was associated with greater compliance. Ecological footprint awareness was the most significant determinant of sustainable dietary practices, highlighting the importance of combining polyphenol-rich foods with strategies that enhance environmental consciousness to promote public health and sustainability.